GE_GERICHTE P/17823/2012 vom 11. Oktober 2013 - GE Cour de justice (2013)
FIXATION DE LA PEINE; CONCOURS D'INFRACTIONS; SURSIS À L'EXÉCUTION DE LA PEINE; RÉVOCATION(EN GÉNÉRAL) | CP.47; CP.42.1; CP.46.1; CP.49.1; CP.42.2